Natural history and clinical detection of undiagnosed coeliac disease in a North American community. Issue 10 (25th March 2018) - Hujoel, I. A.; Van Dyke, C. T.; Brantner, T.; Larson, J.; King, K. S.; Sharma, A.; Murray, J. A.; Rubio‐Tapia, A.
Summary: Background: Coeliac disease is a substantially underdiagnosed disorder, with clinical testing currently guided by case finding. Aim: To determine the presence of indications for diagnostic testing and frequency of clinical testing in undiagnosed coeliac disease. Methods: This was a case‐control study of adults without prior diagnosis of coeliac disease. Undiagnosed cases were identified through sequential serology, and unaffected age‐ and gender‐matched controls were selected. Medical records were systematically reviewed for indications for and evidence of clinical testing. Results: Of 47 557 adults, 408 cases of undiagnosed coeliac disease were identified. 408 serology negative matched controls were selected. Eight‐matched pairs were excluded, leading to 800 included individuals (61% female; median age 44.2 years). The odds of any indication for clinical testing were similar among undiagnosed coeliac disease and controls (odds ratio (OR) 1.18; 95% CI: 0.85‐1.63, P = 0.32). Most individual indications were not associated with serologic status. Exceptions to this include hypothyroidism, which was more likely in cases of undiagnosed coeliac disease, and dyspepsia and chronic diarrhoea, which were less likely. Cases of undiagnosed coeliac disease were more likely to develop osteoporosis ( P = 0.005), dermatitis herpetiformis ( P = 0.006), chronic fatigue ( P = 0.033), thyroiditis ( P = 0.003), autoimmune diseases ( P = 0.008), and have a family member diagnosed with coeliac disease ( P = 0.001). Conclusion: This study strongly suggests that current case finding is not effective in detecting undiagnosed coeliac disease. Individuals with undiagnosed coeliac disease were more likely than controls to develop indications for testing overtime. A more effective method for detection of coeliac disease is needed. Abstract : Linked Content This article is linked to Lebwohl and Green paper. To view this article visithttps://doi.org/10.1111/apt.14670 .